What is known about parasitic interaction in Limnoperna fortunei (Dunker, 1857) in the Lower Rio Grande Basin (Research, Society and Development, 2022)
Limnoperna fortunei is an invasive exotic bivalve with high reproductive capacity and geographic distribution. Even after three decades of its introduction in South American waters, knowledge about ecological interactions as parasite/host for the species is still scarce in the literature. Therefore, the aim of this study was to investigate the presence of potential parasites in the golden mussel in the Lower Rio Grande Basin. The first step was the dissection of 1.000 L. fortunei from four stretches of the Rio Grande, where the internal and external demibranchs, mantle, gonads, and foot were inspected. The second stage, occurred by photostimulation (1 halogem lamp, 60W, 1 warm white fluorescent lamp 20 W and cool white fluorescent lamp 20 W) where 100 mollusks were exposed, distributed in four species, L. fortunei, C. fluminea, M. tuberculate and a single native representative P. canaliculata. No parasites were found in the exotic bivalve L. fortunei dissected and photostimulated. These results were extended to the other two exotic species C. fluminea and M. tuberculate. Only one specimen of the native species P. canaliculata showed a prevalence of cercaria of less than 1%. In view of these results, we can infer that the absence of parasites in the exotic mollusks and the presence in the native species may be an indication of some level of relationship with the dilution effect hypothesis. This is based on the premise that parasite pressure is diluted in the face of host diversity and the enemy release hypothesis which suggests that exotic species leave their natural enemies behind.